Pre-hospital Emergency Notification System - Xiong, Foo Kian (Universiti Teknologi PETRONAS, 2014)
The number of death cases is increasing annually due to the increasing number of population in the country while the quality of medical healthcare is not progressing fast enough to ensure the quality of life. One of the factor causes the mortality of people is the lack of appropriate pre-hospital care provided. The effectiveness of pre-hospital care is important to reduce the death risk of severe cases like road accident and heart attack. The author proposes a mobile application which allows the emergency medical team to notify the hospital about the incoming victim’s personal information and medical condition. It also provides a web-based system used by hospital staff to view the incoming victims. Rapid Application Development is used in this project. The prototype has been developed using App Inventor 2, PHP and MYSQL. A mock-up database of the victim personal information is stored in MYSQL.